Website Designing As A Media For Promotion And Information On Karang Setio Batik(Perancangan Website Sebagai Media Promosi Dan Informasi Pada Batik Karang Setio) - Firdaus; Nico Alvio Maiyendra; Ritna Wahyuni (Universitas Putra Indonesia YPTK Padang, 2020)
Ads that will be created and displayed must have a good, unique appearance that can attract the attention of consumers and be dynamic in accordance with the fields managed by the company. Website as a medium of promotion and information has enormous benefits. First, consumers do not need to come directly to the store to see and choose the items they want to buy. Second, in terms of financial consumers can save costs incurred, if the store location is far away. The product ordering target is stronger, not only for certain regions. There is no promotion done by Karang Setio Batik Studio, either in the promotion of television advertising, radio or website, making this household industry less well known and visited by many people. And also in the transaction process is still manually with the opportunity to come to the store. Because it needs to be overcome by promoting and providing information using promotional media and website-based information, and also makes it easier to conduct transactions between stores and customers. And it can be concluded that the old system used is not effective and will cause the process carried out will take time and place so that makes employee performance less efficient and effective and results in reports that are not accurate and accurate. This research was conducted by applying a framework or research method that starts from identification of problems, problem analysis, set goals, study literature, collecting data, system design, system testing, and system implementation. By utilizing the development of technology and functions of internet promotion and website-based information as one of the marketing strategies in business development at Karang Karang Setio.